The Correct Qur’anic Readings in Tafsir Al-Baidawi (T: 685 AH) Surat Ibrahim - Collection and Direction - - Abdullah, Abdullah; Khalaf , Abdullah; Ali, Muhammad (Islamic Sciences Journal, 2023)
Praise be to Allah who fulfilled his righteous grace, and peace be upon the final prophet with which Allah sealed the messages, and upon his family and companions and those who followed them with kindness until the Day of Miqat, and after: This research deals with collecting and directing the correct Qur’anic readings in (Tafsir al-Baidawi called: Anwar al-Tanjul wa Asrar al-Ta'wil) Surat Ibrahim. I followed the inductive approach, by following the sayings of Imam al-Baidawi in listing the verses in which the correct readings were mentioned, collecting and directing them, The analytical method, is represented in studying the verses in which the correct readings are contained, verifying them from the books of approved recitations, and directing them by relying on books of arguments, causes, language and morphology books, etc, dividing these verses into paragraphs and putting a number in front of each verse I have investigated.